2013
DOI: 10.1007/s10295-013-1260-z
|View full text |Cite
|
Sign up to set email alerts
|

A multi-factors rational design strategy for enhancing the thermostability ofEscherichia coliAppA phytase

Abstract: Despite recent advances in our understanding of the importance of protein surface properties for protein thermostability,there are seldom studies on multi-factors rational design strategy, so a more scientific, simple and effective rational strategy is urgent for protein engineering. Here, we first attempted to use a three-factors rational design strategy combining three common structural features, protein flexibility, protein surface, and salt bridges. Escherichia coli AppA phytase was used as a model enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Reports on phytase reengineering comprise improved thermostability (directed evolution and semi-rational design approaches) to match demands in the feed pelleting process (60-80°C). We recently reported two experiments improving Ymphytase thermostability (Shivange et al 2014;Shivange et al 2012), and only four other reports on bacterial phytase (α/ß-fold) improvement by directed evolution are available (Fei et al 2013;Zhao et al 2010;Zhu et al 2010). The residual activity of E. coli phytases (appA) was improved by 23.3 % (80°C for 5 min) (Zhu et al 2010), and appA2 phytase was improved by 20 % (80°C for 10 min) in directed evolution experiments using error-prone PCR for diversity generation.…”
Section: Discussionmentioning
confidence: 96%
“…Reports on phytase reengineering comprise improved thermostability (directed evolution and semi-rational design approaches) to match demands in the feed pelleting process (60-80°C). We recently reported two experiments improving Ymphytase thermostability (Shivange et al 2014;Shivange et al 2012), and only four other reports on bacterial phytase (α/ß-fold) improvement by directed evolution are available (Fei et al 2013;Zhao et al 2010;Zhu et al 2010). The residual activity of E. coli phytases (appA) was improved by 23.3 % (80°C for 5 min) (Zhu et al 2010), and appA2 phytase was improved by 20 % (80°C for 10 min) in directed evolution experiments using error-prone PCR for diversity generation.…”
Section: Discussionmentioning
confidence: 96%
“…However, to cut the labor-associated cost of the high false-positive rate of non-rational methods, a number of rational protein engineering methods were established. Rational strategies such as molecular dynamics (MD) simulation [11,19] and structural dynamics [20,21] have been applied to redesign thermophilic proteins. Based on the crystal structure and rational cascade methods, Fei et al constructed a series of engineered phytases, and the mutants showed a great increase of heat resistance compared to the wild-type [19].…”
Section: Introductionmentioning
confidence: 99%
“…Rational strategies such as molecular dynamics (MD) simulation [11,19] and structural dynamics [20,21] have been applied to redesign thermophilic proteins. Based on the crystal structure and rational cascade methods, Fei et al constructed a series of engineered phytases, and the mutants showed a great increase of heat resistance compared to the wild-type [19]. Furthermore, under the guidance of 3D structural information, analysis and calculation of some types of molecular bonds, such as hydrogen bonds [22], salt bridges [23] and disulfide bonds [24], have also been utilized to improve the heat and pH resistance of phytase.…”
Section: Introductionmentioning
confidence: 99%
“…In another report, the authors identified uncharged residues in the highly flexible areas on the protein surface with molecular dynamic simulation and 3D structures. Then, these unstable residues were mutated to form salt bridges to neighboring residues [57]. The selected mutants with higher residual activity at 80°C were further mutated to carry the previous identified I405L.…”
Section: Structure-based Designmentioning
confidence: 99%